Transformasi Pemikiran Sosial Masyarakat Malaysia daripadaFitrah Pertama kepada Fitrah Kedua Mengenai Alam Sekitar: Transformation Social Thought Community of Malaysia From First To Second Nature Of Environmental - Aziz, Azmi; Mokhtar, Mostafa Kamal (GEOGRAFI, 2014)
This article is divided into three social thought major transition: from the beginning of humanlife, a change of the interaction between humans and the environment and, finally, characterizesthe interactions between humans and the environment. This article also discusses the nature ofhistorical perspective first and second nature. The influence of the nature of the first and secondnature to the environment in Malaysia was infused briefly in this article. This article shows thatMalaysia is a multiracial society that is very unique. This means that Malaysian society is a societyaccepts and appreciates the disposition first. The arrival of colonial and imperial west has brought anew paradigm to a community known as second nature whichis contrary to nature first. However,Malaysians are able to harmonize the clash between the two this nature.